Can vocabulary lessons increase the amount of complex syntax produced by head start teachers? A pilot study. (October 2017) - Van Horne, Amanda Owen; Curran, Maura; Hall, Jessica
In this pilot study, we examine the suitability of materials for a vocabulary intervention designed to influence the amount of complex syntax teachers use in at-risk preschool classrooms. Six Head Start classrooms were assigned to one of two vocabulary interventions: a condition using cognitive verbs, which are biased toward complex syntax (e.g. pretend), or a control condition using action verbs, which are biased towards simple sentences (e.g. identify). Consistent with our hypotheses, teachers in the cognitive verb condition used higher rates of complex syntax than those in the action verb condition while our materials were in use. Teacher acceptability and use data indicate that verb characteristics affect frequency of use and perceived benefit of intervention materials. Implications for the development of interventions targeting complex syntax use in at-risk children are discussed, including factors likely to support fidelity of implementation in the classroom.